2013
DOI: 10.1016/j.hjdsi.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Global budgets and technology-intensive medical services

Abstract: Background In 2009-2010, Blue Cross Blue Shield of Massachusetts entered into global payment contracts (the Alternative Quality contract, AQC) with 11 provider organizations. We evaluated the impact of the AQC on spending and utilization of several categories of medical technologies, including one considered high value (colonoscopies) and three that include services that may be overused in some situations (cardiovascular, imaging, and orthopedic services). Methods Approximately 420,000 unique enrollees in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Recent private payer reforms such as the Alternative Quality Contract have begun to show some success in decreasing use of low‐value services (Song et al. ). Innovative bundled payments, such as the PROMETHEUS payment model and the Geisinger ProvenCare model, also aim to reduce costs and improve quality (de Brantes, Rosenthal, and Painter ; Paulus ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent private payer reforms such as the Alternative Quality Contract have begun to show some success in decreasing use of low‐value services (Song et al. ). Innovative bundled payments, such as the PROMETHEUS payment model and the Geisinger ProvenCare model, also aim to reduce costs and improve quality (de Brantes, Rosenthal, and Painter ; Paulus ).…”
Section: Discussionmentioning
confidence: 99%
“…Private payers have similar contracts and increasingly are holding providers accountable for cost and quality, paralleling Medicare attempts to reduce low-value care. Recent private payer reforms such as the Alternative Quality Contract have begun to show some success in decreasing use of lowvalue services (Song et al 2013). Innovative bundled payments, such as the PROMETHEUS payment model and the Geisinger ProvenCare model, also aim to reduce costs and improve quality (de Brantes, Rosenthal, and Painter 2009;Paulus 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no evidence of the effectiveness of any single payment model as a tool for reducing overuse specifically. At a high level, however, the evidence suggests that risk sharing reduces use and total cost, [55][56][57] whereas pay for performance has had a much more mixed record of success. 58 A critical question for the ongoing research on global and bundled payment initiatives (eg, Medicare's Accountable Care Organizations Shared Savings Program and Bundled Payment for Care Initiative) is whether these approaches, which effectively encourage reduction in costs regardless of value, have a disproportionate effect on overuse.…”
Section: Opportunities For Reformmentioning
confidence: 99%
“…The AQC, which incorporates global budget and pay‐for‐performance principles, began in 2009 with 7 physician organizations in Massachusetts and had 15 participating groups by 2012 (Song et al. ). Investigators found that the AQC was associated with spending reductions of 1.9 and 3.3 percent in its first and second years, respectively, along with evidence of improvements in quality.…”
Section: Cutting Fat or Muscle?mentioning
confidence: 99%
“…Analysis of Blue Cross Blue Shield of Massachusetts' Alternative Quality Contract (AQC) does as well (Song et al 2011(Song et al , 2012. The AQC, which incorporates global budget and pay-for-performance principles, began in 2009 with 7 physician organizations in Massachusetts and had 15 participating groups by 2012 (Song et al 2013). Investigators found that the AQC was associated with spending reductions of Hospital Cost Shifting and Productivity 1.9 and 3.3 percent in its first and second years, respectively, along with evidence of improvements in quality.…”
Section: Cutting Fat or Muscle?mentioning
confidence: 99%